PENYELESAIAN KASUS TERHADAP KORBAN GAS ELPIJI DALAM PERSPEKTIF UNDANG UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUGAN KONSUMEN - , Amanda, SH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As known that in 2007 the government was launched conversion policy on petrol to Liquid Petroleum Gas (LPG). The aim of the conversion is to save public budget expense and decrease pollution level. Jusuf Kallaâs statement when he was the Vice President that conversion program of subsidized energy from petrol to 3 kg size-LPG will save Oil Fuel subsidy in APBN amount 30 billion IDR with only 15 billion investments. The research on solving of The Liability of PERTAMINA toward Liquid petroleum gas Victims in the Perspective of Act Number 8 Year 1999 On Costumer Protection, using juridical normative approach. Normative law research established through literature study on secondary data, or known as library research. In 8mei 2007 Conversion program of petrol to LPG planned by the government creates problems that cannot be avoided. The problem is exploded phenomenon of gas tube caused by some things, such as pipe. Pertamina is an institution that is considered has responsibility. In fact, Pertamina is only responsible in gas tube foundation, while the completeness as rubber pipe that will be connected to gas furnace is other institutionsâ responsibility.The phenomenon of gas tube explosion has been harmed lower middle class costumers. The injury is ranging from light to mortality. Paragraph above indicated that the related ministry is Industrial Ministry who also responsible for petroleum and natural gas. In Paragraph 5 of Republic Indonesia Regulation no. 104, 2007 concerning Supply. that is LPG tube, so Pertamina must be liable. PT. Pertamina who as producer and regulator official of 3 kgs LPG marketing must be liable if there is any fault that causing a loss of life or material from the product that produced, in this case is gas tube.